The natural history and morphology of two bromeliad associated hispines from Brazil: Acentroptera basilica Thomson, 1856 and A. cf. tessellata Baly, 1958 (Coleoptera: Chrysomelidae: Cassidinae: Sceloenoplini) - Albertoni, Fabiano F.; Casari, Sônia A. (Zootaxa, 2017)
The natural history of Acentroptera basilica Guérin-Méneville, 1844 and A. cf. tessellata Baly, 1958 (Cassidinae: Sceloenoplini) associated with Aechmea aquilega Salisb. and Vriesea sp. (Bromeliaceae), respectively, is registered. Adults of both species are leaf scrapers, although larvae are leaf-miners. The immature stages of both species of Acentroptera are described and illustrated for the first time. The male and the female genitalia of A. basilica and new records for both species are also included.